Variations in arterial pedal circulation in idiopathic congenital talipes equinovarus: a systematic review. Issue 1 (January 2021) - Puri, Aiysha M.C.; Hughes, Katie P.; Stenson, Katherine M.; Gelfer, Yael; Holt, Peter J.E.; Patterson, Benjamin O.
Abstract : Variations in pedal circulation in congenital talipes equinovarus (CTEV) are well documented. There is a reported risk of vascular injury to the posterior tibial artery (PTA) during operative procedures for CTEV, potentially leading to necrosis and amputation. The aim of this systematic review was to identify the most common anomalies in arterial pedal circulation in CTEV and to determine the relevance of these to clinical practice. The systematic review was registered on PROSPERO and was carried out according to Preferred Reporting Items for Systematic Reviews and Meta Analyses guidelines by two independent reviewers. Studies that examined pedal circulation in idiopathic CTEV were included. Articles that studied nonidiopathic CTEV and those not published in English were excluded. Data extracted included patient demographics, imaging modalities, and findings. A total of 14 articles satisfied the inclusion criteria, including 192 patients (279 clubfeet), aged 0–13.5 years, at various stages in their treatment. Imaging modalities included arteriography ( n = 5), duplex ultrasound ( n = 5), magnetic resonance angiography ( n = 2), and direct visualization intraoperatively ( n = 2). The dorsalis pedis was most frequently reported as absent (21.5%), and the anterior tibial artery (ATA) was most frequently reported as hypoplastic (18.3%). Where reported ( n = 36 feet), 61% of patients were noted to have a dominant supply from the PTA. The most common variation in pedal circulation in CTEV is diminished supply from ATA and dorsalis pedis, although there are documented anomalies in all of the vessels supplying the foot. We therefore recommend routine Doppler ultrasound imaging prior to operative intervention in CTEV. Abstract : Supplemental Digital Content is available in the text.